Experimental Study on Flotation of a Micro-fine Arsenopyrite-type Gold Ore in Central Asia - Wenpu ZHANG; Xiaohui WANG; Weilong WU; Kunxi HUANG; Kaile ZHAO; Zhen WANG (Kuangchan zonghe liyong)
Against the backdrop of increasing global gold demand and the depletion of easily treatable gold resources, the development of refractory gold ores has become increasingly important. A gold deposit in Central Asia, characterized by large reserves, low sulfur, high arsenic, and low-grade refractory gold ore, with an Au grade of 1.53 g/t and ultra-fine gold dissemination (over 60% of particles smaller than 0.01 mm), was studied. Comparative beneficiation tests showed that the single flotation process outperformed the combined shaking table-flotation process. The closed-circuit flotation test employed a short-flow process of "one roughing, one scavenging, and two cleaning" stages, in combination with the addition of a novel organic composite depressant EMY-515 and a new composite collector EMB-906. This resulted in a gold concentrate with an Au grade of 40.20 g/t and a recovery rate of 76.44%, while the Au content in the tailings was reduced to 0.37 g/t. This study provides a feasible solution for the development of this type of gold ores and offers technical support for the efficient exploitation and utilization of gold resources in countries along the "Belt and Road" initiative.